The Effect of Family and Peer Environments on Students' Career Planning - Savira, Firda; Puji Sugiharto, Dwi Yuwono; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2022)
Career planning is an important medium to achieve success in the world of work because it leads people to the careers they are living. Thus, this study attempted to analyze the effect of family and peers’ environments on students’ career planning. It used a quantitative method by using correlation and regression techniques. Of 5,967 students, 374 were taken using cluster random sampling. Their data were collected using the scales of family environment, peers and career planning. Findings showed that there found the effects of a family environment on career planning (β=0.690 t=8.522 p<0.01), peers on career planning (β=0.217 t=2.623 p<0.01) and the family environment and peers simultaneously on students' career planning (R=0.558 R2= F=83,711 p<0.01). This study has clarified the role of the family environment and peers on students' career planning.